Association between body roundness index and female infertility: a cross-sectional study of NHANES 2013–2018 - Li, Haiyan; OuYang, Zhenbo; Ding, Ziyao; Hu, Xianyue; Bao, Yanjing; Gao, Tianyang; Hua, Wenfeng (Frontiers in Nutrition, 2024)
BackgroundThe use of visceral obesity as an indicator for predicting female infertility risk has not been well established. The body roundness index (BRI) is a novel, non-invasive indicator of visceral fat; however, previous reports have not addressed the relationship between the BRI and female infertility. This study sought to fill this research gap by investigating the association between the BRI and the risk of female infertility.MethodsThis cross-sectional study examined 3,528 women aged 18 to 45 who participated in the National Health and Nutrition Examination Survey (NHANES) from 2013 to 2018. Infertility was defined based on responses to the reproductive health questionnaire. The BRI was calculated using waist circumference and height. Covariates included demographic traits, physical exam results, laboratory test findings, and survey data. Weighted multivariable logistic regression models and spline smoothing analysis assessed the relationship between the BRI and infertility. Bayesian statistics were used to examine the robustness of significant associations.ResultsBased on their self-report data, 407 (11.54%) participants were classified as having infertility. A significantly higher percentage of participants with a higher BRI were found to have infertility. Multivariable logistic regression revealed that the BRI was significantly associated with increased female infertility risk, regardless of independent variable analysis by continuous variable or quartile (Q1 to Q4) in the fully adjusted model (Model 3, continuous variable: OR = 1.1, 95% confidence interval [CI] = 1.05–1.16, p = 0.0009; Q4 vs. Q1: OR = 2.16, 95% CI = 1.38–3.39, p = 0.0035, Ptrend = 0.004). Non-linear and threshold effects in the relationship between the BRI and female infertility were identified, with an inflection point of 6.36. Subgroup analyses showed that this positive association remained consistent across most demographic and health-related categories. The Bayesian statistics analyses further confirmed the robustness of these findings.ConclusionA positive non-linear relationship exists between the BRI and the risk of female infertility, suggesting that the BRI could serve as a valuable indicator in female fertility assessments.